Une nouvelle étude architecturale du temple romain de Harf Chlifa, Btedai (Liban) - Kahwagi-Janho, Hany (Syria, 2023)
A new architectural study of the Roman temple at Harf Chlifa, Btedai (Lebanon)Abstract - The sanctuary of Harf Chlifa, locally known as Qasr el-Banat, occupies the tip of a rock formation that stands out from the eastern flanks of Mount Lebanon and juts out into the Bekaa plain. The site includes, installed within a temenos surrounded by a temenos wall, an in antis distyle temple from the Roman period as well as an apsidal monument and a set of structures added later as part of a transformation of the places in the Byzantine period. The site was visited and documented by D. Krencker and W. Zschietzschmann in 1903 and in 1933. Damaged during the Lebanese war (1975-1990), it was the subject of a new documentary study carried out within the framework of an academic workshop at the Holy Spirit University of Kaslik (USEK), which allowed a better documentation and understanding of the site and its transformations. This study has made it possible to assign a new order (Ionic) to the temple, to reconstruct its original appearance and to confirm its rather high dating, following a comparative study with similar regional monuments.